Vitamin and Some Mineral Substance Levels along with Hematological Findings in Cattle with Tongue Rolling Disease - Issi, Mustafa; Ozcelik, Mehtap; Gul, Yusuf (Kafkas Univ, Veteriner Fakultesi Dergisi, 2009)
The purpose of this study was to determine hematological findings and some mineral substance [Zinc (Zn), copper (Cu), iron (Fe), cobalt (Co), manganese (Mn)] and vitamin (A, C, beta-carotene) levels in tongue rolling disease which is very common in the animals in the region. Study material consisted of a total of 25 animals collected from three family enterprises in the counties of Elazig province. Fifteen of these cattle were observed to have tongue rolling (Patient group) and 10 of these cattle of the same age and origin were clinically healthy with no tongue rolling anamnesis (Control Group). It was found that the hematological findings and vitamin levels in the patient and control group cattle was between normal physiologic values and that the difference between the groups was insignificant (P>0.05). It was found that the meaning values Cu and Mn was found to be significantly (respectively P<0.01, P<0.001) low in patient group animals even though the difference between the groups of Zn, Fe and Co meaning values in the patient and control group was not statistically significant (P>0.05). Consequently, we conclude that tongue rolling disease in cattle may be caused by Mn and Cu deficiency and these elements should be added to the rations of the animals which show tongue rolling symptoms.
Dil oynatma hastalıklı sı?ırlarda hematolojik bulgularla birlikte bazı mineral madde ve vitamin düzeyleri
Keywords: Tongue rolling; Hematolojik findings; Trace element; Vitamin; Cattle